0
$\begingroup$

Use mathematical induction to prove that $$1\cdot3+2\cdot4+3\cdot5+...+n(n+2)≥ \frac{1}{3}(n^3+5n)$$ for $n≥1$.

I have tried this and got what I thought was the correct answer but it doesn't work for all values of n greater than 1. Any help would be greatly appreciated.

$\endgroup$
  • $\begingroup$ Why don't you post what you have tried so we can see where you may have gone wrong? $\endgroup$ – mrp Jan 8 '15 at 10:08
  • 1
    $\begingroup$ I have proved that p(1) is true, and written out the formulas for p(k) and p(k+1). I now have 1/3(k^3+5k)+(k+1)(k+3)>orequalto 1/3((k+1)^3+5(k+1)) by using the assumption that p(k) is true. If this is correct (which I'm not sure of) then I eventually get down to the inequality 3k>orequalto -1 which is obviously correct for k>orequalto 1. Any thoughts? Thanks x $\endgroup$ – Alex Jan 8 '15 at 10:10
1
$\begingroup$

Your reasoning is correct. Assumnig $p(k)$ true, $p(k+1)$ is equivalent to $$ \frac{1}{3}(k^3+5\,k)+(k+1)(k+3)\ge\frac{1}{3}((k+1)^3+5(k+1)), $$ which reduces to $$ 12\,k+9\ge3\,k+6. $$ This is clearly true for all $k\ge1$.

$\endgroup$
1
$\begingroup$

Another chance is given by just computing the LHS. $$\begin{eqnarray*} \sum_{n=1}^{N} n(n+2) &=& \sum_{n=1}^{N}\left((n+1)^2-1\right) = -N+\sum_{n=2}^{N+1}n^2 = -(N+1)+\sum_{n=1}^{N+1}n^2\\&=&-(N+1)+\frac{(N+1)(N+2)(2N+3)}{6}=\color{red}{\frac{N(N+1)(2N+7)}{6}}.\end{eqnarray*}$$ So, we just have to check that $(N+1)(2N+7)\geq 2(N^2+5)$ for any $N\geq 1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.